Managerial Handling of Zeigarnik Effect on Job Satisfaction and Work Performances of Employees - Soomro, Athar Hussain; Tunio, Shahnawaz; Khatyan, Azad Ali; Khooharo, Tanveer Ahmed (The journal of contemporary issues in business and government, 2021)
This research finds out that how the manager should handle their employees with Ziegarnik effect to measure their outcomes at their work in order to assess their degree of happiness and satisfaction, because higher the work outcomes would ultimately define organizational Success. While on other hand, interruptions may have some negative impacts. In this study,mostly middle line managers were targeted from different associations and data were collected through questionnaire survey method from 160 workers through convenient sampling technique. The study is quantitative in nature andthe results were put to the test using regression analysis, which shows that managerial handling of Zeigarnik effect is positively related to the “employee work performance” and “job satisfaction”. This means that higher the managerial handling of Zeigarnik effect, the better would be the employees performance and job satisfaction. It is recommended to enhance some techniques for handling job stress and creating interest in job duty.